2020
DOI: 10.1016/j.sleep.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on sleep and mental health of patients with Parkinson's disease during the Coronavirus disease 2019 pandemic

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic is adversely affecting sleep quality and mental health, especially in individuals with chronic disease such as Parkinson's disease (PD). Methods We conducted a quantitative study, which included 119 Chinese PD patients who had been treated in an outpatient neurology clinic in Wuhan and 169 age- and sex-matched healthy controls. The questionnaire survey focused on the impact of the COVID-19 pandemic on sleep, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(96 citation statements)
references
References 31 publications
3
93
0
Order By: Relevance
“…In addition, we showed that a male sex was associated with clinical anxiety, while a female sex was reported to be a potential risk factor for anxiety both in general population and in PD patients [ 26 , 27 ]. In the previous report, Xia et al showed lower scores of depression and anxiety in male PD patient than female, though it was not multivariate analysis [ 10 ]. In addition, we are currently under the distinct stress due to COVID-19 pandemic that did not exist in the past, so we need more cases to determine the impact of sex on the neuropsychiatric symptoms under COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we showed that a male sex was associated with clinical anxiety, while a female sex was reported to be a potential risk factor for anxiety both in general population and in PD patients [ 26 , 27 ]. In the previous report, Xia et al showed lower scores of depression and anxiety in male PD patient than female, though it was not multivariate analysis [ 10 ]. In addition, we are currently under the distinct stress due to COVID-19 pandemic that did not exist in the past, so we need more cases to determine the impact of sex on the neuropsychiatric symptoms under COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…No minors were among the participants. According to a priori power analysis (with 95% power and 5% type I error rate) of the results of previous studies [ 8 10 ], the minimum number for the sample was found to be 41 patients for the comparative study of the prevalence of psychiatric symptoms during COVID-19 pandemic in PD and control groups. This study was a cross-sectional, single hospital-based survey conducted from April 22, 2020 to May 15, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Our data confirm the findings of other studies that investigated the psychological impact of COVID-19 on PD patients, highlighting significant emotional sequelae of the pandemic. In particular, depression was previously reported to occur in 21% of patients, and anxiety in a percentage ranging from 21 to 81.7% of patients [ 17 ] and in 57.9% of caregivers [ 5 ]. In addition, increased distress was reported in 43.8% of patients and 53.1% of caregivers [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Xia et al investigated how the pandemic has affected sleep and mental health of patients with PD in comparison to healthy controls. 43 Results of their study showed that 68.9% of the PD patients suffered from sleep disturbance, a much higher rate than that of the general population. Further evidence shows that scores from the Hamilton Anxiety and Depression Scale on PD patients with sleep disturbances were significantly higher than PD patients who did not experience sleep disturbances, indicating that anxiety and depression are important factors affecting PD patients' sleep quality during the pandemic.…”
Section: Nonmotor Symptomsmentioning
confidence: 98%
“…Further evidence shows that scores from the Hamilton Anxiety and Depression Scale on PD patients with sleep disturbances were significantly higher than PD patients who did not experience sleep disturbances, indicating that anxiety and depression are important factors affecting PD patients' sleep quality during the pandemic. 43…”
Section: Nonmotor Symptomsmentioning
confidence: 99%